Bio-inspired formation of nanostructured arrays on flexible substrates with superoleophobicity12. Issue 44 (13th October 2015) - Meng, Xinghua; Deng, Da
Abstract : A bio-inspired synthesis of nanoarrays on a flexible substrate using Mn3 (PO4 )2 ·3H2 O as a model is demonstrated and achieves superoleophobicity. Abstract : Nanomaterials with size- and structure-dependent properties have attracted much attention recently. However, it is still challenging to achieve large-scale fabrication of nanostructured arrays on flexible substrates at room temperature. Here, we report a facile procedure, inspired by eggshell formation, to synthesize high-order nanostructured flake arrays on a flexible Nafion membrane. We demonstrated, using Mn3 (PO4 )2 ·3H2 O as a model, that a cation exchange Nafion membrane can function as a controller of cations and pH to provide the appropriate reaction environment for the nucleation and formation of rectangle-shaped Mn3 (PO4 )2 ·3H2 O nanoflake arrays directly grown on the Nafion membrane substrate at room temperature. The bio-inspired approach offers a facile procedure for the large-scale synthesis of various nanostructures, in principle, at room temperature. The formation mechanism was investigated by tuning the experimental parameters. Interestingly, we also demonstrated that the hierarchical structures of the nanoflake arrays on flexible substrates showed impressive underwater superoleophobicity, similar to that of fish scales.